A Pilot Study of the Effect of a Change in the Scheduling of Canadian Medical Licensing Examinations on Two Cohorts of Students Studying in Ireland - Niethammer, Kate; Gouda, Pishoy; Moylett, Edina (International Journal of Medical Students, 2015)
Background: The Medical Council of Canada and most Canadian residency programs require international medical graduates seeking training in Canada to pass the Medical Council of Canada Entrance Examination, in addition to the newly established National Collaborative Assessment. In order to facilitate this additional examination, the Medical Council of Canada has altered the suggested examination timeline and examination eligibility criteria. Methods: A cross-sectional survey was sent via an online survey tool to members of the North American Irish Medical Student Association. The survey aimed to elicit differences in the Medical Council of Canada Entrance Examination experience between two cohorts of Canadians studying abroad in Ireland: those who completed the examination before and after the new timeline. Statistical analysis was conducted with independent t-tests and Pearson’s Chi-Square tests using SPSS version 21. Results: Of 24 respondents, 13 had completed the examination after the timeline change. Participants who attended the examination prior to the change achieved higher results (353.8 ± 56.5) than participants who attended the examination after the change (342.3 ± 35.1), although not statistically significant (p=0.56). In the cohort who took the examination after the timeline change, 61.5% of participants expressed discontent with their examination results; 84.6% ‘strongly agreed’ or ‘agreed’ to feeling disadvantaged due to the change. Conclusion: The new Medical Council of Canada examination timeline has had an impact on the examination experience of Canadians studying in Ireland. Simple modifications to the current timeline are warranted to reduce unnecessary disadvantage for this cohort of students applying to postgraduate training...